The Additional Value of Endolymphatic Hydrops Imaging With Intratympanic Contrast for Diagnostic Work-Up—Experience From a Neurotology Center in Austria - Weitgasser, Lennart; O‘Sullivan, Anna; Schlattau, Alexander; Roesch, Sebastian (Frontiers in Surgery, 2021)
Objective: To illustrate the merit of hydrops imaging during clinical workup of dizziness and balance disorders. Background: Ever since the first description of in-vivo endolymphatic hydrops imaging in 2007, this diagnostic tool has been implemented in an increasing number of centers. The more experience in its clinical application is gathered, the more it is possible to critically assess its potential value for the diagnostic workup. This article intends to provide information about the experience of handling and utilization of endolymphatic hydrops imaging in one of the first centers in Austria. Methods: Retrospective analysis and review of clinical cases. Results: Based on our experience of endolymphatic hydrops imaging (EHI), which was established in cooperation between our departments of radiology and otorhinolaryngology in 2017, we have exclusively used intratympanic application of a contrast agent prior to magnetic resonance imaging, as this approach provides high quality imaging results. In 42.6% of cases, EHI could lead to the diagnosis of MD or HED. Since precise vestibular examination is still necessary, EHI is not a tool to replace the clinical examination but rather to add significantly to the interpretation of the results. Conclusion: Endolymphatic hydrops imaging represents a valuable, safe and well-applicable tool for evaluating cases with inconclusive clinical results. However, its potential additional diagnostic benefits rely on a correct indication based on prior thorough vestibular investigations.